Reclaimed - Roux, Madeleine, 1985- (Ace, 2021)
"In this claustrophobic science fiction thriller, a woman begins to doubt her own sanity and reality itself when she undergoes a dangerous experiment. The Ganymede compound is a fresh start. At least that's what Senna tells herself when she arrives to take part in a cutting-edge scientific treatment, where participants have traumatic memories erased. And Senna has reasons for wanting to escape her past. But almost as soon as the treatment begins, Senna finds more than just her traumatic memories disappearing. She hardly recognizes her new life or herself. Even though the symptoms for the process might justify the cure, Senna knows that something isn't right. As her symptoms worsen, Senna will need to band together with the other participants to unravel the mystery of her present, and save her future"--